Impact of COVID-19 Case Numbers on the Emission of Pollutants from a Medical Waste Incineration Plant - Monika Załuska; Anna Justyna Werner-Juszczuk; Katarzyna Gładyszewska-Fiedoruk (Aerosol and Air Quality Research)
Abstract This article examines the correlation between the amount of pollutants emitted from medical waste incinerator plant and the number of COVID-19 infections, based on the example of Podlaskie Voivodeship in Poland. This paper deals with the issues of medical waste management during the COVID-19 pandemic. Thermal processing is characterised as a method of medical waste utilisation. The technological sequence of the medical waste incineration installation and the integrated exhaust gas cleaning system are discussed. The results of studies on the emission of pollutants into the atmosphere during combustion are compared with the number of COVID-19 cases in the same voivodeship to investigate how the coronavirus pandemic affects the amount of medical waste generated, thus the amount of pollutants emitted into the atmosphere. The Pearson’s linear correlation coefficient and the Student’s t-test are used to verify the results. The analysis results show a statistically significant, moderate positive correlation between the amount of covid waste and the number of COVID-19 cases (0.5140). In turn, there is also a statistically significant moderate correlation between the number of COVID-19 cases and emissions of SO2 (r = 0.6256, p = 0.010), NOx (0.5019, p = 0.048), and HCl (0.5130, p = 0.042). This correlation finding highlights additional costs to the environment and public health as the number of COVID-19 cases increase, which can be taken into account for pandemic planning by governments in the future.